Candida colonization of the vagina of HIV-seropositive pregnant women and their seronegative counterparts at selected health-care centers in Akure, Ondo State, Nigeria - Ebhodaghe, BlessingItohan; Ako-Nai, Kwashie Ajibade; Aderoba, Adeniyi; Anderson, WinstonA; kassem, Olakunle O (Annals of Tropical Medicine and Public Health, 2023)
International Article of Annals of Tropical Medicine and Public Health,VOL;9,Issue;6,Page;10